Palisaded encapsulated neuroma clinically mimicking a mucocele: report of a case - John Lennon S. Cunha; Amanda F. Silva; Raimundo S. Rocha; Ericka Janine D. Silveira; Ricardo Luiz C. Albuquerque Jr (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT We report the case of a 21-year-old female patient with the chief complaint of a small tumor on the lower left lip. Intraoral examination revealed a two-month evolution nodular lesion on the left labial mucosa, of resilient consistency and asymptomatic. A history of prior trauma was reported by the patient. A provisional diagnosis of mucocele was established, and an excisional biopsy was performed. The diagnosis was palisaded encapsulated neuroma (PEN). As PEN is considered underdiagnosed by many authors, a discussion on the morphologic diagnostic criteria of this lesion will be provided.